A study on knowledge attitude and practice of contraception in school going children in Wardha district in central India - Jain, Manish; Jain, Shuchi; Patil, Shubhangi; Bang, Akash (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Adolescent sexuality is leading to adolescent pregnancy, unsafe abortion, Reproductive Tract Infections, Sexually transmitted infections. Therefore, studying knowledge, attitude and practice regarding this problem among school adolescents is an essential issue, which can support to overcome young people from sexual related problems. Methods: This study was cross sectional study conducted in Wardha district of Maharashtra among school going adolescents. Data was collected by the means of anonymous questionnaire after taking the informed consent. Results: In our study total 375 students were included in the study, amongst 192 were girls and 183 were boys. Majority of students belong to age group of 13-15 years. Nearly 50% of students were knowing about basic reproductive physiology. Amongst the total 375 participants, 184 (49%) students had ever heard about any of contraceptive method while 51 % of totally unaware. Among total students having knowledge of contraception, 38.7% knew about condoms, oral contraceptive pills as method of contraception were known to 88 students (23.5%) while knowledge of emergency contraception was very low. The knowledge of females was higher as compared to males regarding oral and emergency contraception. 15% of total adolescents accepted that they have used condom. The proportion of males using condoms was higher as compared to females. Conclusions: The adolescents need to be provided with correct knowledge for behavior change, to stop their undesirable practices for healthy life. There was an evident gap between knowledge and practices with respect to the sexual practices of youth which needs to be bridged.